Student Self-Concept and Achievement Motivation of High School Students - Ihda Husnayaini (IAIN Syaikh Abdurrahman Siddik Bangka Belitung, 2019)
Learning English have been challenging for many students in Bangka Belitung, especially for vocational school students. This can be related to the students’ self-concept. Self-concept refers to an individual’s overall self-awareness. Self-concept is particularly important in studies related to education and learning because a lot of studies suggested that it has a correlation with academic achievement. This study was aimed to find out whether there is a correlation between the student self-concept and achievement motivation using the sample of high school students in Bangka Belitung. The findings suggested that the students had a good self-concept - especially when it comes to self-regard and parental acceptance aspects and positive achievement motivation. Those two aspects depict their self-image and self-esteem, the two most dominant components in self-concept. Regarding gender, the writer did not find any significant difference between female and male students in terms of self-concept and academic achievement. However, it was found that there was no correlation between self-concept and achievement motivation. This can be influenced by different characters, backgrounds, situations and expectations each student had. Belajar Bahasa Inggris telah menjadi tantangan bagi banyak siswa di Bangka Belitung, terutama bagi siswa sekolah kejuruan. Hal tersebut dapat terkait dengan konsep diri siswa. Konsep diri mengacu pada kesadaran diri individu secara keseluruhan. Konsep diri sangat penting dalam studi yang berkaitan dengan pendidikan dan pembelajaran karena banyak penelitian menunjukkan bahwa konsep diri memiliki korelasi dengan prestasi akademik. Penelitian ini bertujuan untuk mengetahui apakah ada hubungan antara konsep diri siswa dan motivasi berprestasi dengan menggunakan sampel siswa sekolah menengah kejuruan di Pangkalpinang, Bangka. Hasilnya menunjukkan bahwa siswa-siswa tersebut memiliki konsep diri yang baik - terutama yang berkaitan dengan aspek harga diri dan penerimaan orang tua dan juga memiliki motivasi berprestasi yang positif. Kedua aspek tersebut menggambarkan citra diri dan harga diri mereka, dua komponen yang paling dominan dalam konsep diri. Mengenai jenis kelamin, peneliti tidak menemukan perbedaan yang signifikan antara siswa perempuan dan laki-laki dalam hal konsep diri dan prestasi akademik. Namun, hasil penelitian menunjukkan bahwa tidak ada korelasi antara konsep diri dan motivasi berprestasi. Hal tersebut bisa jadi dipengaruhi oleh karakter, latar belakang, situasi dan harapan yang beragam yang dimiliki oleh setiap siswa.